Implementation of the Sabaq, Sabqi, Manzil Methods in Improving the Quality of Memorizing Qur'an Learning in Class V Salafiyah Ula Islamic Center Bin Baz Bantul - Shodikin, Eko Ngabdul; Edi Sucipto; Achadi, Muh. Wasith; Farih Muzaky; Rizkyana Wahyu Laras Pertiwi (International Journal of Post Axial: Futuristic Teaching and Learning, 2023)
The research focuses on the significant role of Sabaq, Sabqi, and Manzil methods in the Taḥfīẓul Qur’ān learning process. These methods are essential in helping individuals achieve their desired targets in Qur’ān memorization while ensuring consistency. Several educational institutions widely adopt these popular methods. The study's main objectives are twofold: (1) to comprehend how the implementation of Sabaq, Sabqi, and Manzil methods occurs in the Taḥfīẓul Qur’ān learning process at Class V Salafiyah Ula Islamic Centre Bin Baz during the Academic Year 2022/2023, and (2) to determine the effectiveness of these methods in the same setting. The research follows a qualitative approach with data collected through observations, interviews, and documentation. The implementation of the Sabaq, Sabqi, and Manzil methods in the Taḥfīẓul Qur’ān learning process comprises five stages: planning and preparation, implementation, monitoring, evaluation, and reflection. The findings indicate that the effectiveness of these methods at Class V Salafiyah Ula Islamic Centre Bin Baz during the Academic Year 2022/2023 is satisfactory. Though some students haven't achieved their targets, the application of these methods has successfully increased students' engagement with the Qur’ān compared to previous approaches. Additionally, the methods contribute to maintaining balanced memorization of both new and previously learned verses of the Qur’ān. In conclusion, the study highlights the crucial role of Sabaq, Sabqi, and Manzil methods in the Taḥfīẓul Qur’ān learning process. The research offers insights into their implementation and effectiveness, providing valuable information for educators and institutions seeking to enhance the memorization of the Qur’ān among their students.